Unpacking the Nature of Orchestrator Coherence in Entrepreneurial Ecosystems - Bonomi Santos, Juliana; Fischer, Bruno Brandão; Cherubini Alves, André; Roundy, Philip T. (Entrepreneurship Theory and Practice, 2025)
Despite its importance to the functioning of entrepreneurial ecosystems (EEs), the orchestration of networks remains a largely undertheorized topic. To address this “omission,” we sought to explain the interplay between networks, their orchestrators, and their implications for ecosystem outcomes. To do so, we conducted an in-depth case study of the Agtech Valley EE in Brazil. From our study, we developed theoretical insights on the notion of “ecosystem coherence” as a foundational driver of EE structuration. Findings revealed two dimensions of ecosystem coherence: capabilities coherence (based on organizational and cognitive proximities) and relationship coherence (based on institutional and social proximities).